INTERNALIZATION OF MULTICULTURAL ISLAMIC EDUCATION VALUES BASED ON LOCAL WISDOM: A QUALITATIVE CASE STUDY OF THE BOOK OF MARAH LABID, SURAT MARYAM AYAT 12-15 BY SHEEKH NAWAWI AL BANTANI - Cato, Cato; Firdaus, Slamet; Asmuni, Ahmad; Fatimah, Siti (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: This research is based on the urgency of strengthening multicultural Islamic education in Indonesia's complex social, cultural, and religious diversity. In this context, the classic commentary on Marah Labid by Sheikh Nawawi al-Bantani is seen as relevant as an authoritative source for exploring fundamental values ​​that can be internalized in the world of education. Purpose of this research is to identify the values ​​of multicultural Islamic education contained in the commentary, while analyzing its implementation strategies in schools based on local wisdom. This research uses a qualitative method with a bibliographic and hermeneutic approach, supported by a case study of implementation at MA Asyafi'iyyah Karangasem, Margasari District. Results show that verses 12–15 of Surah Maryam, as interpreted in Marah Labid, contain values ​​of empathy, social concern, obedience, discipline, humility, and religious integration with local culture. These values ​​are implemented through collaborative learning strategies, consistent daily practices, teacher role models, and local wisdom-based innovations such as project-based learning, Islamic educational games, and arts and culture integration. The impact is seen in the formation of students' religious, inclusive, tolerant, and socially conscious characters, both at school, at home, and in the community. Conclusion of this study confirms that the integration of classical Nusantara interpretations with modern educational practices based on local wisdom can strengthen character education and multiculturalism, making it relevant to addressing the challenges of contemporary Islamic education while maintaining the nation's cultural identity.